Answer:
(-3, 4, 6)
Explanation:
-3x-4y+z=-1 equation 1
2x+y-z=-8 equation 2
x+8y-z=23 equation 2
Add equation 1 and 2
-3x-4y+z=-1
2x+y-z=-8
-----------------------
-x -3y = -9 equation 4
Add equation 1 and 3
-3x-4y+z=-1
x+8y-z=23
--------------------
-2x + 4y = 22 equation 5
multiply equation 4 by -2
2x + 6y = 18
Now add it with equation 5
2x + 6y = 18
-2x + 4y = 22
-----------------------
10y = 40
divide by 10 on both sides
y = 4
Plug in y = 4 in equation 4
-x -3y = -9
-x - 3(4) = -9
-x -12 = -9
add 12 on both sides
-x = 3
x=-3
plug in x=-3 and y =4 in any one of the original equation
-3x-4y+z=-1 equation 1
-3(-3) -4(4) +z= -1
9 -16 +z=-1
-7 + z= -1
add 7 on both sides
z = 6